(3LQjeI GdEVQGQ ZjQ GdYeOj HGdCehGd Ch GdeUGdM GdYGeI (B: s (3OQGSI ebGQfI (B/ s - (3eLOj YHO GdcQje YKeGf GdLhNjs; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2013)
(3jJfGhd GdHMK cGaI GdLhGfH GdbGfhfjI GdeQJHWI HLQjeI GdEVQGQ ZjQ GdYeOj, GdefUhU YdjgG HGdeGOI (B116 (3ecQQG (B((3C(B) (3ef bGfhf GdYbhHGJ, ef MjK CQcGf GdLQjeI h GdTQW GdeaJQV hGdYbhHGJ GdebQQI dgG GdCUdjI hGdJcejdjI hGdXQa GdeTOO, hWHjYI gPg GdLQjeI HGYJHGQgG ef LQGFe GdNWC ZjQ GdYeOj, h JMOjO YdGbI gPg GdLQjeI HGdeSFhdjI GdJCOjHjI, eY YQV GdJWhQ GdJTQjYj ddMeGjI GdLfGFjI ddeGd GdYGe aj GdbGfhf GdhVYj, h JMOjO UaI GdLGfj cehXa YGe aj cdG ef GdbGfhf GdLfGFj hGdbGfhf GdEOGQj(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2013.s
(3HHdjhLQGajG(B: (3UaMGJ (B303-315.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdMeGjI GdLfGFjIs; (3GdGehGd hGdeUGdM eMd GdMeGjI ai LQjeI GdGVQGQ ZjQ GdYeOis; (3UaI GdLGfi ai LQjeI GdGVQGQ ZjQ GdYeOis; (3GdQcf GdeGOi dLQjeI GdGVQGQ ZjQ GdYeOis; (3GdQcf GdeYfhi dLQjeI GdGVQGQ ZjQ GdYeOis; (3eGgjI GdNWG ai LQjeI GdGYeGd ZjQ GdYeOis; (3GdYbhHI GdGUdjI hGdYbhHI GdJcejdjI dLQjeI GdGVQGQ ZjQ GdYeOis; (3GdXQha GdeTOOI dLQjeI GdGVQGQ ZjQ GdYeOi s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs